2023
DOI: 10.3390/ijms24065338
|View full text |Cite
|
Sign up to set email alerts
|

Knockout Mutants of OsPUB7 Generated Using CRISPR/Cas9 Revealed Abiotic Stress Tolerance in Rice

Abstract: Plants produce and accumulate stress-resistant substances when exposed to abiotic stress, which involves a protein conversion mechanism that breaks down stress-damaged proteins and supplies usable amino acids. Eukaryotic protein turnover is mostly driven by the ubiquitination pathway. Among the three enzymes required for protein degradation, E3 ubiquitin ligase plays a pivotal role in most cells, as it determines the specificity of ubiquitination and selects target proteins for degradation. In this study, to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Interestingly, pub mutants reported to be affected in drought resilience were both hyper- or hypo-sensitive: single gene mutants of the Arabidopsis paralogs AtPUB46 and AtPUP48 (Adler et al 2017), and the Atpub8 mutant (Adler 2011) are drought hypersensitive whereas Arabidopsis Atpub18, Atpub19, Atpub23 , and Atpub24 mutants exhibit increased drought tolerance compared with wild-type plants (Seo et al 2012). Also, the rice OsPUB7 knockout mutant and the Ospub41 suppression mutant, and Ubi:RNAi-OsPUB41 knock-down lines showed enhanced survival to drought (Kim et al 2023; Seo et al 2021). (Despite sharing a common gene name OsPUB41 is not orthologous to AtPUB41 , but shows the highest similarity to AtPUB20 and AtPUB21 ).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, pub mutants reported to be affected in drought resilience were both hyper- or hypo-sensitive: single gene mutants of the Arabidopsis paralogs AtPUB46 and AtPUP48 (Adler et al 2017), and the Atpub8 mutant (Adler 2011) are drought hypersensitive whereas Arabidopsis Atpub18, Atpub19, Atpub23 , and Atpub24 mutants exhibit increased drought tolerance compared with wild-type plants (Seo et al 2012). Also, the rice OsPUB7 knockout mutant and the Ospub41 suppression mutant, and Ubi:RNAi-OsPUB41 knock-down lines showed enhanced survival to drought (Kim et al 2023; Seo et al 2021). (Despite sharing a common gene name OsPUB41 is not orthologous to AtPUB41 , but shows the highest similarity to AtPUB20 and AtPUB21 ).…”
Section: Resultsmentioning
confidence: 99%
“…The concerns about introducing foreign genes into plants are eliminated in this technique as it precisely edits the target gene at nucleotide level without any transgene intervention [142]. Knockout mutants of diverse genes involved in abiotic stress response created by the CRISPR technique resulted in enhanced tolerance in a range of species such as rice [143], tomato [144], tobacco [145], soybean [146], and wheat [147]. To ensure the gene stability in the modified plants, a lipofection-mediated delivery into protoplasts [148] was developed along with other approaches such as Agrobacterium-mediated transformation [149] and particle bombardment [150].…”
Section: Use Of New Technologies To Improve Crop Stress Tolerancementioning
confidence: 99%
“…CRISPR/Cas9 employed targeted mutagenesis in the OsRR22 was improved the salinity tolerance in the japonica rice cultivar WPB106 . Kim et al (2023) paved the way of generating targeted mutagenesis in the gene OsPUB7 through CRISPR/Cas9 to develop drought tolerance and abiotic stress rice in the future. Alam et al (2022) reported that knocking out the OsbHLH024 transcription factor conferred salinity tolerance.…”
Section: Biotic and Abiotic Stressmentioning
confidence: 99%